Acceptability of a community health worker intervention to improve the oral health of older Chinese Americans: A pilot study. (27th December 2020) - Northridge, Mary E.; Wu, Yinxiang; Troxel, Andrea B.; Min, Deborah; Liu, Rong; Liang, Li Juan; Metcalf, Sara S.; Seyedzadeh Sabounchi, Shabnam; Yi, Stella
Abstract: Objective: To evaluate the acceptability of a community health worker (CHW) intervention designed to improve the oral health of low‐income, urban Chinese immigrant adults. Background: Given that both dental caries and periodontitis are behaviourally mediated, biofilm‐based diseases that are largely preventable with attention to regular oral hygiene practices and preventive dental visits, strategies to arrest or even heal carious lesions and high‐quality maintenance care and plaque control without the need to resort to aerosol‐generating surgical approaches are evidence‐based best practices. Older immigrants have poorer oral health than older US‐born natives, motivating the need for delivery of more effective and affordable services to this vulnerable population. Materials and Methods: CHWs were trained by the NYU College of Dentistry dental hygienist faculty members using dental models and flip charts to instruct patients on proper brushing and flossing techniques. In addition, they discussed the presented oral health promotion information one‐on‐one with patients, addressed any expressed concerns and encouraged prevention of oral conditions through regular dental visits and brushing with fluoride toothpaste. Results: More than 98% of the 74 older Chinese adult participants strongly agreed/agreed that the CHWs helped them to improve how they take care of their health, the CHWs answered their questions and concerns, the information and topics were informative, and the in‐person demonstrations were helpful in improving oral health. Conclusion: The health of all communities depends on access to comprehensive care, including oral health care, in the wake of COVID‐19. CHW interventions are acceptable to and may reach marginalised and immigrant communities.